2002
DOI: 10.1159/000063321
|View full text |Cite
|
Sign up to set email alerts
|

Heminephrectomy Causes the Progression of Glomerulosclerosis and Apoptosis in High IgA Strain ddY Mice

Abstract: Background: The reduction in nephrons in IgA nephropathy is critical to the prognosis of this disease. However, the immunopathological mechanism of the modifications seen in glomerular lesions is not clear. We thus investigated the influence of nephron reduction by heminephrectomy on renal lesions in a high immunoglobulin A inbred strain of ddY mouse (HIGA mouse), which shows progressive mesangial sclerosis with elevated renal expression of transforming growth factor (TGF)-β. Methods: Five-week-old HIGA mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Nephron reduction by heminephrectomy is known to enhance glomerular injury in several animal models (21)(22)(23)(24)(25)(26)(27). In this study, using a podocyte-specific transgenic HIVAN mouse line, we demonstrated that removal of one kidney dramatically accelerated podocyte injury and led to severe glomerulosclerosis.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Nephron reduction by heminephrectomy is known to enhance glomerular injury in several animal models (21)(22)(23)(24)(25)(26)(27). In this study, using a podocyte-specific transgenic HIVAN mouse line, we demonstrated that removal of one kidney dramatically accelerated podocyte injury and led to severe glomerulosclerosis.…”
mentioning
confidence: 66%
“…There was marked progression in renal injury after 8 to 16 wk. In some experimental animal models, heminephrectomy accelerates renal injury (21)(22)(23)(24)(25)(26)(27). To test the hypothesis that nephron reduction enhances podocytes injury and accelerates collapsing glomerulopathy, we heminephrectomized podocin/Vpr mice 1 wk before the administration of doxycycline (Figure 2A).…”
Section: Heminephrectomy Accelerates Hivanmentioning
confidence: 99%
“…4) Glomerular angiotensin convertase enzyme (ACE) in unilateral nephrectomized mice was significantly enhanced, and this enhancement suggests that the increase in the intraglomerular blood pressure might be caused by the progression of renal damage. 4) However, this study showed that captopril, a representative ACE inhibitor, failed to improve histopathological changes in an accelerated model of IgA nephropathy. Thus, the results suggest that the progression of a model combining unilateral nephrectomy, reticuloendothelial system blockade, and oral administration of bovine g globulin may not depend on intraglomerular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, unilateral nephrectomy, blockade of the reticuloendothelial system, and oral sensitization in ddY mice have demonstrated that the deposition of IgA and pathological changes in glomeruli may be induced earlier than those in spontaneous ddY mice. [3][4][5] Transforming growth factor-b1 (TGF-b1) induces matrix synthesis in renal tissues, leading to the progression of IgA nephropathy. 6,7) When added to cultured human mesangial cells, aggregated IgA1 from patients with IgA nephropathy induces increases in TGF-b1 gene expression and secretion of extracellular matrix in cultured mesangial cells.…”
mentioning
confidence: 99%
“…In addition, the expression of TGF-␤ in the kidney was shown to be increased in these mice (21). Moreover, HIGA mice show a remarkable glomerular deposition of matrix components such as fibronectin and collagen IV (22). These findings suggest that HIGA mice may provide a valuable model for studying the mechanisms of chronic sclerosis developing types of IgAN.…”
Section: Discussionmentioning
confidence: 82%